1999
DOI: 10.1002/(sici)1096-9861(19990726)410:2<277::aid-cne9>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of glutamic acid decarboxylase mRNA in the forebrain of the rainbow trout as studied by in situ hybridization

Abstract: By using degenerate primers designed from glutamate decarboxylase (GAD) sequences of mammals, Xenopus and Drosophila, a 270‐bp cDNA fragment was cloned by reverse transcriptase‐polymerase chain reaction (RT‐PCR) from cerebellum total RNA of rainbow trout. This partial cDNA shows 90% identity with mammalian GAD 65 and presents the Asn‐Pro‐His‐Lys (NPHK) sequence corresponding to the pyridoxal‐binding region of porcine DOPA decarboxylase or mammalian GAD. The distribution of GAD 65 mRNA‐expressing neurons in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 73 publications
5
16
0
Order By: Relevance
“…In the anterior preglomerular nucleus (F) of the masu brain, we found GABA-ergic type-I neurons. The results of immunohistochemical labeling of GABA in nuclei of the masu preglomerular complex agree with the data obtained on other fish species [23][24][25]. In the glomerular nucleus, considerable amounts of GABA/ benzodiazepine receptors were found [26].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the anterior preglomerular nucleus (F) of the masu brain, we found GABA-ergic type-I neurons. The results of immunohistochemical labeling of GABA in nuclei of the masu preglomerular complex agree with the data obtained on other fish species [23][24][25]. In the glomerular nucleus, considerable amounts of GABA/ benzodiazepine receptors were found [26].…”
Section: Discussionsupporting
confidence: 88%
“…In the medial and anterior nuclei of the preglomerular complex of the Danio fries, neurons with expresion of the vesicular transporter GAD67 were found [23]. Medina et al also found GABA-ergic neurons in the preglomerular complex of the silver eel (Anguilla anguilla) [24], while GAD was found in the trout preglomerular nucleus [25]. Taking into account these data, we can suppose that GABA does not exclusively function in the masu preglomerular complex as a neuromodulator/neuromediator; this agent can also be considered a factor controlling the morphogenesis in this region.…”
Section: Discussionmentioning
confidence: 96%
“…We did not observe at any stage Lhx6-positive cells that could constitute the fish counterpart of tangentially migrating GABAergic cortical interneurons (Anderson et al, 1999;Anderson et al, 1997;Anderson et al, 2001;Marin and Rubenstein, 2001;Marin and Rubenstein, 2003). In fish, these GABAergic pallial interneurons constitute a relatively scarce neuronal population (Anglade et al, 1999), and the absence of pallial Lhx6 expression, together with the absence of Dlx gene expression in the fish pallium (Akimenko et al, 1994;Alunni et al, 2004;Zerucha and Ekker, 2000) (present data), suggest that these interneurons do not share common genetic specification mechanisms with their mammalian counterparts. In fact, an Lhx6.1 isoform of Lhx6 in mouse was reported to be expressed both in the cortex and the olfactory bulbs .…”
Section: Lhx6: a Marker For A Subpallium To Pallium Migratory Stream supporting
confidence: 45%
“…The distribution of GABAergic cells has been investigated in the forebrain of the eel (Medina et al, 1994), trout (Anglade et al, 1999) and goldfish (Martyniuk et al, 2007). These studies focused on the distribution of GABAergic cells in telencephalic and hypothalamic regions and did not lead to an improved anatomical characterization of subpallial units to distinguish among striatum, pallidum and septum as recently discussed (Wullimann and Mueller, 2004b).…”
Section: Introductionmentioning
confidence: 99%